“ASSESS THE EFFECTIVENESS OF STRUCTURED TEACHING PROGRAMME ON KNOWLEDGE REGARDING SELFCARE AMONG ADOLESCENT GIRLS” - Gaurav Kumar; Chetna Vashishth; Bibha Kumari; Shalini Devi; Satish Prajapti (The Bioscan, 2025)
Teenagers within the ages of 10 and 19 are considered teenagers by the World Health Organization, or WHO. It is sometimes referred to as "growing-up decades" or "not at all youngsters not grownups." The Latin term "adolescent," which means "to develop" or "to mature," is the root of the English word "adolescence." Life is a dynamic process in which a different stage comes and every stage of life comes with different problems. Adolescent is a period of transition between childhood and adulthood. Teenage girls are a particularly susceptible group, especially in India, where female children are often ignored. In Indian culture, menstrual is still seen as filthy or disgusting. Awareness and understanding of the topic are necessary for the response to menstruating. The method through which a girl understands about her menstruating and its related changes one may have an impact on her response to the event of menarche. Despite being a normal occurrence, menstruation is associated with a number of myths and behaviors that might occasionally have a negative impact on one's well-being.